Classicist Development of FATHER-SON Topos in “The Adventures of Telemachus” by Fénelon - A. E. Baretskaya (Научный диалог)
This article analyzes the “father-son” topos in “The Adventures of Telemachus” by Fénelon in relation to the cultural-historical situation and philosophical-aesthetic achievements of the 17th century. It explores the complex interactions of mythological motifs and the results of their individual-authorial artistic embodiment in Fénelon’s novel. The basis for understanding the “father-son” topos in a new anthropological paradigm is revealed, focusing on the image of the evolving individual capable of justifying the historical possibility of a more rational social structure. The influence of the philosophical and ethical situation of the era on the interpretive characteristics of the topos in the novel is determined. The evolution of the traditional archaic image of the epic hero is traced with a shift in roles. It is argued that the novel depicts not only traditional mythological tests of strength but also new “psychological” tests arising from changes in the philosophical-ethical situation: loneliness, love, power. The study’s novelty lies in identifying the author’s ideological stance shaping the topos “the ruler’s love for his people as for a son.” The research confirms the thesis of the determining influence of worldview attitudes of the era and cultural coordinates on the historical fate of the topos as a literary phenomenon.